Prevalence of ecto- and endoparasites of the Sea bass Dicentrachus Labrax in Port Said Governorate, Egypt. - Tadros, S.W.A., A.K. El-Gayar & E.M. Abouelhassan (Egyptian Journal of Aquatic Biology & Fisheries, 2020)
The Sea bass (Dicentrachus labrax) is consider one of the most important seawater fish species of South Europe and Mediterranean aquaculture . In the present study; we investigated the parasitism of Sea bass in Port Said Governorate, Egypt during the period from October 2016 till October 2017 . A total number of 100 sea bass (ranged from 300 to 400 gm weight) were collected randomly; the parasitological examination showed a total of 9 different parasite species were found. The ectoparasites were represented by two copepods (Caligus elongates and Lernanthropus psciaenae) with 28% total prevalence, one isopod species (Levonica redmani) infestation rate was 16%, and one monogenean species; Diplectanum aequans which showed the highest infection rate (64%). Five species of digenean were found with a total prevalence of 36%; they were (Acanthostomum spiniceps, Erilepturus Hamati, Stephanostomum murielae, Creptotrema creptotrema, and Aponurus mulli). The highest total prevalence of infestation among the examined fish was in autumn (60%) and the lowest was in summer (24%), while in winter and spring the prevalence rates were 48% and 36% respectively.